Perencanaan dan Proses Pemasaran yang dilakukan Xpander - Nala Agustin; Hendra Riofita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to analyze the strategic planning and implementation of the Mitsubishi Xpander marketing process in an effort to increase market share and sales. The method used in this research is a literature review which includes theoretical analysis, research results and relevant references to provide an in-depth understanding of the topic discussed. The results of the discussion show that Mitsubishi Xpander has succeeded in standing out in the multi-purpose vehicle (MPV) segment through appropriate market segmentation, product development that focuses on safety and comfort, and a competitive pricing strategy. Diverse promotions and efficient distribution through the official dealer network also contribute to marketing success. Additionally, the company highly values ​​customer feedback, which is an important pillar for product innovation and continuous improvement. The implications of this research emphasize the importance of integration between strategic management and marketing in creating competitive advantage. By understanding consumer needs and adapting to market dynamics, Mitsubishi Xpander can continue to increase the relevance and attractiveness of products in an increasingly competitive automotive industry.